Comparison of the crystallization behavior of Fe-Si-B-Cu and Fe-Si-B-Cu-Nb-based amorphous soft magnetic alloys - Smith, Casey (2014)
The role of the solute elements, copper, and niobium, on the different stages of de-vitrification or crystallization of two amorphous soft magnetic alloys, Fe73.5Si13.5B9Nb3Cu1, also referred to as FINEMET, and a Fe76.5Si13.5B9Cu1 alloy, a model composition without Nb, has been investigated in detail by coupling atom probe tomography and transmission electron microscopy. The effects of copper clustering and niobium pile-up at the propagating interface between the α-Fe3Si nanocrystals and the amorphous matrix, on the nucleation and growth kinetics have been addressed. The results demonstrate that while Cu clustering takes place in both alloys in the early stages, the added presence of Nb in FINEMET severely restricts the diffusivity of solute elements such as Cu, Si, and B. Therefore, the kinetics of solute partitioning and mobility of the nanocrystal/amorphous matrix interface is substantially slower in FINEMET as compared to the Fe76.5Si13.5B9Cu1 alloy. Consequently, the presence of Nb limits the growth rate of the α-Fe3Si nanocrystals in FINEMET and results in the activation of a larger no. of nucleation sites, leading to a substantially more refined microstructure as compared to the Fe76.5Si13.5B9Cu1 alloy.